Moebius syndrome - improving outcome with combined state-of-the-art surgical and rehabilitation treatments - Castro, João Paulo (2021)
Moebius Syndrome (MBS) is a rare disorder, characterized by congenital, non-progressive facial palsy and other cranial and limb defects. A typical “mask-like” appearance, drooling, and indistinct speech comprise the dominant features. Treatment focuses on correcting deformities and enhancing functionality. Surgical free functional muscle transfer (FFMT) is the gold standard for facial reanimation. A comprehensive rehabilitation program addressing motor, cognitive, and social impairment is paramount, despite the scarcity of knowledge regarding MBS rehabilitation, especially concerning central nervous system reorganization. A six-year-old boy with MBS received treatment in our Department since the age of four months, including speech, physical, and occupational therapy. Recently, he underwent facial reanimation surgery. The authors believe that rehabilitation improved the patient’s outcome by enhancing cortical representation before and neuroplasticity after surgery. Coordination of both interventions seems pivotal to fully address MBS.